2019
DOI: 10.1038/s41598-019-46866-6
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic signatures of germination triggered by kinetin in Medicago truncatula

Abstract: In the present work, non-targeted metabolomics was used to investigate the seed response to kinetin, a phytohormone with potential roles in seed germination, still poorly explored. The aim of this study was to elucidate the metabolic signatures of germination triggered by kinetin and explore changes in metabolome to identify novel vigor/stress hallmarks in Medicago truncatula . Exposure to 0.5 mM kinetin accelerated seed germination but impaired seedling growth. Metabolite composition wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 66 publications
0
18
0
Order By: Relevance
“…The next step was to examine the expression patterns of genes that play roles in DNA repair and antioxidant defense, previously used as indicators of seed quality during the early stages of germination (namely seed imbibition) [5][6][7][8]. This is a rather important aspect because such molecular indicators allow the prediction of seed quality in a very short time, thus providing assistance to Seed Companies to design customized priming protocols [2,3,9,10].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The next step was to examine the expression patterns of genes that play roles in DNA repair and antioxidant defense, previously used as indicators of seed quality during the early stages of germination (namely seed imbibition) [5][6][7][8]. This is a rather important aspect because such molecular indicators allow the prediction of seed quality in a very short time, thus providing assistance to Seed Companies to design customized priming protocols [2,3,9,10].…”
Section: Discussionmentioning
confidence: 99%
“…In our previous works, we reported that genes playing roles in DNA repair and antioxidant responses can be used as indicators of seed quality and seeding growth [5][6][7][8]. Here we focused on the expression patters of OGG1 (8-Oxoguanine DNA glycosylase) and FPG (Formamidopyrimidine-DNA glycosylase), involved in Base Excision Repair (BER), APX (Ascorbate peroxidase) and SOD (Superoxide dismutase), encoding known ROS scavengers, and MT2 (Metallothionein type 2), proven to act both as ROS scavenger and repair enzyme [41].…”
Section: Expression Patterns Of Genes Involved In Dna Repair and Antimentioning
confidence: 99%
See 2 more Smart Citations
“…As different metabolic pathways are being reactivated during seed imbibition, in previous works we monitored the changes in metabolite profiles using a non-targeted metabolomics approach (Pagano et al, 2019;Araújo et al, 2019). From the generated datasets, here we have extrapolated only the changes in the carbohydrate metabolic pathway since trehalose is included in this category (Figure 3).…”
Section: Seed Imbibition Triggers Changes In the Expression Of Genes mentioning
confidence: 99%